A comparison of n-alkane contents in sediments of five lakes from contrasting environments. (January 2020) - Zhang, Yongdong; Yu, Jinlei; Su, Yaling; Du, Yingxun; Liu, Zhengwen
Highlights: Profiles of n -alkanes in sediments were dependent on water column structure, nutrient inputs and catchment disturbance. In deep lakes, non-photosynthetic bacterial and aquatic macrophytes were major contributors of n -alkanes. Terrestrial plant sourced n -alkanes were exceptionally abundant in alpine lakes. Eutrophication driven enrichment of short-chain odd carbon n -alkanes was recorded in shallow lakes. Abstract: In paleolimnology studies, the trajectories of n -alkane abundances and distributions in dated sediments are widely used indicators of changing environmental and ecological status in the overlying water over time. However, the factors contributing to the variable n -alkane profiles of lake systems are not yet fully understood. Here, a comparative study was conducted to examine natural and anthropogenic influences on the sediment n -alkane profiles of five representative lakes in China. Core samples from the deep oligo- mesotrophic lakes Fuxian and Lugu (FX-1 and LG-1 cores), the shallow eutrophic lakes Taibai and Changdang (TB-1 and CD-1 cores) and the alpine Lake Heihai (HH-1 core) were used. While there were striking differences in n -alkane abundances and distributions between the cores, the results suggested that the n -alkanes in all five studied lakes were derived mainly from biogenic sources, rather than from petroleum contamination. The short-chain (20 ) even carbon n -alkanes, assumed to derive from non-photosynthetic bacteria, were especially prevalent in FX-1, reaching 158.3–284.4 μg/g TOC, which might be a result of high levels of bacterial productivity in the deep (average 89.6 m) water column of Lake Fuxian. The contribution of bacterial production diminished in the other four lakes, with 20 n -alkanes declining to between 21.4 and 60.5 μg/g TOC on average in the studied cores. In the two shallow lakes, abundances of short-chain (20 ) odd carbon n -alkanes were greatly elevated in sediments corresponding to the eutrophic phase; for example, with maximum values of 136.3 μg/g TOC recorded in TB-1. This nutrient-driven effect was less apparent in deep lakes. The >C21 n -alkane profiles of different cores varied significantly. Abundances of long-chain n -alkanes (C29, C31 and C33 ) in HH-1 were approximately 3–7 times greater than in other cores. Coupled with the lowest Paq (average 0.29) values recorded in the study, this indicates a predominantly terrestrial plant origin for the >C21 n -alkanes, most likely the dense alpine meadow which surrounds the lake. In other cores, however, aquatic macrophytes appear to be more important contributors of the n -alkanes, a result that corresponds with the relatively low density of terrestrial plants in those catchments.